Rice Pests and Diseases Around the World: Literature-Based Assessment with Emphasis on Africa and Asia - Sofia Conde; Sílvia Catarino; Sónia Ferreira; Marina Padrão Temudo; Filipa Monteiro (Agriculture)
Rice is a vital staple crop for global food security, yet a worldwide comprehensive assessment of pests and diseases remains lacking. This study aims to (1) identify globally reported pests and diseases, (2) analyze their distribution patterns, and (3) assess their impact on rice productivity. A literature-based assessment with an initial pool of 15,969 articles from three online databases (PubMed, WOS, and CAB Abstract) resulted in 871 articles for analysis. The findings highlight a regional focus on Africa and Asia, where rice is predominantly produced. Pest occurrence varies across continents, with Diopsis, Maliarpha, and Chilo being prevalent in Africa, while Nilaparvata, Scirpophaga, Sogatella, and Chilo dominate in Asia. Key pathogens differ across regions, with Pyricularia, Xanthomonas, and Sobemovirus in Africa, while Fusarium and Bipolaris are common in Asia. Major yield losses are attributed to Pyricularia (Blast disease), Bipolaris (Brown Spot), Fusarium (Bakanae), and Sobemovirus (Rice Yellow Mottle Virus). The lack of data from major rice producers like Myanmar highlights reporting gaps, urging future research. This study enhances the global understanding of rice pest and disease distribution and their impacts on productivity. It could also support early warning systems and assess the effectiveness of control methods in the context of climate change.